ON MIRTEMIR'S POETIC SKILLS (Scientific journal of the Fergana State University, 2023)
The article covers the issues of the subject scale and artistry of Mirtemir’s poetry. The methodological features of the poet’s poetry, the scale of the image were studied. The role and significance of Mirtemir’s works in the development of Uzbek poetry of the 20th century is shown.